Antistatic sea-island fiber
Patent Information
- Application Number
- JP2022159137
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-09-30
- Filing Date
- 2022-09-30
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2042-09-30
AI Technical Summary
Existing polyester fibers with polyalkylene glycol as an antistatic agent face issues of insufficient antistatic performance, high cost, complex spinning processes, and poor operability due to polyalkylene glycol's low viscosity and tendency to bleed out, necessitating a more effective and cost-efficient antistatic solution.
The development of sea-island fibers with an antistatic agent, such as potassium trifluoromethanesulfonate, confined to the sea portion, achieving high antistatic performance with a specific agent content and cross-sectional area ratio, ensuring good spinning operability and cost-effectiveness.
The antistatic sea-island fibers exhibit excellent spinning operability and antistatic properties, maintaining transparency and reducing agent leakage, while providing sufficient antistatic performance even with a small amount of antistatic agent.
Smart Images

Figure 00000008_0000 
Figure 00000008_0001
Abstract
Description
Technical field
[0001] TECHNICAL FIELD The present invention relates to a sea-island fiber having antistatic properties. [Background technology]
[0002] Polyester fibers are used in a wide range of applications due to their low cost and excellent mechanical properties. However, since polyester is inherently hydrophobic and has high electrical resistance, polyester fibers tend to generate static electricity. Various proposals have been made so far for methods of imparting antistatic properties to polyester fibers in order to overcome this drawback. As a method for imparting antistatic properties, a hydrophilic compound may be added to polyester. A typical example is polyalkylene glycol, and a polyester fiber added with polyalkylene glycol or a resin composition containing polyalkylene glycol as a main component has been proposed. Patent Document 1 discloses polyethylene glycol as an antistatic agent. Containing polyester fibers are described. [Prior art documents] [Patent document]
[0003] [Patent document 1] Japanese Patent Application Laid-Open No. 2016-148132 [Outline of the Invention] [Problems to be solved by the invention]
[0004] However, the fiber described in Patent Document 1 has polyethylene glycol as an antistatic agent dispersed throughout the fiber, so the antistatic performance is insufficient relative to the content of the antistatic agent. When the content of the antistatic agent is increased in order to improve the antistatic performance, there is a problem that the cost becomes high and the spinning operability is deteriorated. In addition, since polyalkylene glycol has a low viscosity and is difficult to mix with the resin forming the fiber, a method of injecting it into the nozzle using a press-fitting machine is preferably used. In this method, before reaching the metering gear pump, polyalkylene glycol is injected with a press-fitting machine, mixed with polyester with a static mixer, the mixture is weighed with a metering gear pump, and discharged from a nozzle. There have been problems such as high costs for management due to the complexity of the process, and poor spinning operability due to unstable press-in amount. In addition, since polyalkylene glycol has a low viscosity, it tends to bleed out on the fiber surface, and when washed, the agent escapes and the antistatic performance decreases. For the above reasons, there is a demand for an antistatic fiber using an antistatic agent other than polyalkylene glycol or a resin composition containing polyalkylene glycol as a main component. Therefore, the present invention provides an antistatic fiber having excellent spinning operability and sufficient antistatic performance even when an antistatic agent other than polyalkylene glycol or a resin composition containing polyalkylene glycol as a main component is used. for the purpose. [Means for solving the problem]
[0005] As a result of intensive studies, the inventors of the present invention have found that sea-island fibers containing a specific amount of antistatic agent only in the sea part can provide a fiber that exhibits sufficient antistatic performance and good workability while suppressing costs. I found that it can be done, and completed the present invention. That is, in order to achieve the above objects, the present invention employs the following configurations. (1) An antistatic sea-island fiber comprising polyester islands, polyester seas, and antistatic sea-island fibers containing polyester and an antistatic agent. The content of the antistatic agent in the whole is 2.2 to 3.3% by mass, the content of the antistatic agent in the sea portion is 4.5 to 6.0% by mass, and the ratio of the area occupied by the sea portion in the cross section of the fiber is 40 to 70%. An antistatic sea-island fiber.
[0006] (2) The antistatic sea-island fiber according to (1), wherein the antistatic agent contains potassium trifluoromethanesulfonate.
[0007] (3) The antistatic sea-island fiber according to (1) or (2), which has a total fineness of 10 dtex or more.
[0008] (4) The antistatic sea-island fiber according to (1) to (3), which has a single filament fineness of 1 to 10 dtex.
[0009] (5) The antistatic sea-island fiber according to (1) to (4) above, wherein the number of island portions is 10 to 40.
Effect of the invention
[0010] According to the present invention, it is possible to obtain an antistatic sea-island fiber having excellent spinning operability, low cost and antistatic properties. [Brief description of the drawing]
[0011]
Figure 1
Figure 2
[0012] The present invention will be described in detail below. The antistatic sea-island fiber of the present invention comprises a plurality of island portions not exposed on the fiber surface and a sea portion covering the island portions.
[0013] The antistatic sea-island fiber of the present invention is an antistatic sea-island fiber containing polyester in the island portion and polyester and an antistatic agent in the sea portion. By containing the antistatic agent only in the sea part, the antistatic performance is high even with a small amount of antistatic agent.
[0014] Polyester in the present invention preferably comprises at least one polymer selected from polyethylene terephthalate, polybutylene terephthalate and poly-p-ethyleneoxybenzoate, and polyethylene terephthalate is particularly preferred.
[0015] The antistatic agent in the present invention is not particularly limited as long as it is not a polyalkylene glycol or a resin composition containing polyalkylene glycol as a main component. It can be appropriately selected from antistatic agents containing coalescence and organic metal salts. It is particularly preferable to use an antistatic agent containing an organic metal salt because the antistatic performance does not depend on temperature and the transparency of the fiber can be maintained. As the antistatic agent containing an organic metal salt, one containing potassium trifluoromethanesulfonate as an organic metal salt is preferred.
[0016] The content of the antistatic agent in the present invention is preferably 2.2-3.3% by mass in the entire fiber. If the content of the antistatic agent in the entire fiber is 2.2% by mass or more, a fiber with high antistatic performance can be obtained, and if it is 3.3% by mass or less, the spinning operability is good. Moreover, it is preferably 4.5 to 6.0% by mass in the sea area. If the content of the antistatic agent in the sea part is 4.5% by mass or more, a fiber with high antistatic performance can be obtained, and if it is 6.0% by mass or less, fiberization is possible.
[0017] The cross-sectional area of the sea portion of the antistatic sea-island fiber of the present invention is preferably 40 to 70%, more preferably 50 to 67%, of the cross-sectional area of the entire fiber. If it is 40 to 70%, excellent spinning operability and sufficient antistatic performance can be obtained.
[0018] The number of island portions in the antistatic sea-island fiber of the present invention is preferably 10 to 40. If the number of island portions is 10 or more, the antistatic performance is likely to be exhibited. If the number of islands is 40 or less, the islands are less likely to fuse during the spinning process, resulting in stable spinning operation.
[0019] The total fineness of the antistatic sea-island fiber of the present invention is preferably 10 dtex or more. If the total fineness is 10 dtex or more, fiberization becomes easy.
[0020] The single filament fineness of the antistatic sea-island fiber of the present invention is preferably 1 to 10 dtex. If the single yarn fineness is 1 dtex or more, fiberization is easy, and if the single yarn fineness is 10 dtex or less, the antistatic performance is excellent. In addition, it becomes possible to manufacture soft clothing when used as a fabric.
[0021] The water content of the polyester and the antistatic agent used in the present invention is preferably 50 ppm or less from the viewpoint of spinning operation. It is preferable that the thinner the single yarn fineness, the stronger the drying.
[0022] The breaking strength of the antistatic sea-island fiber of the present invention is preferably 3.5 cN / dtex or more from the viewpoints of less thread breakage in weaving and knitting, etc., and good process passability in post-processing. More preferably, it is 4.0 cN / dtex or more.
[0023] The breaking elongation of the antistatic sea-island fiber of the present invention is preferably 30% or more from the viewpoints of less thread breakage in weaving and knitting and good passability in post-processing. More preferably, it is 35% or more.
[0024] The antistatic sea-island fiber of the present invention preferably has an initial triboelectric voltage value of greater than -8000V as measured by the following antistatic property evaluation test. If it is higher than -8000V, it can have sufficient performance as an antistatic yarn. <Antistatic property evaluation test> The initial triboelectric charge voltage of the sample is measured according to JIS L 1094 2014 D method (triboelectrification decay measurement method). The measurement conditions are as follows. Triboelectrification measurement: INTEC Co., Ltd. Triboelectrification attenuation measuring device (EST-8) Friction cloth: wool Friction Direction: Longitudinal Laundry processing: With laundry Temperature and Humidity: 20℃ 40%RH
[0025] Examples of the method for producing the antistatic sea-island fiber of the present invention include the conveyor method, the POY method, and the SPD method, but from the viewpoint of labor saving and productivity, it is preferable to adopt the SPD method.
[0026] In the SPD method, the spinning temperature is preferably 280°C or higher. More preferably, the spinning temperature is 290°C or higher. The upper limit of the spinning temperature is preferably about 300°C.
[0027] By using the fabric containing the antistatic sea-island fiber of the present invention as materials for linings of clothing, sheets and the like, these products can be imparted with antistatic properties.
Example
[0028] EXAMPLES The present invention will be specifically described below with reference to Examples. It should be noted that the present invention is not limited to the examples described below. Measurement and evaluation of physical properties were carried out as follows.
[0029] <Antistatic property evaluation test> After scouring the tubular knitted fabric with an aqueous solution of sodium carbonate: 2 g / L and Emulgen 707: 2 g / L at 70 ° C for 20 minutes, the initial friction withstand voltage was measured by the above-mentioned JIS L 1094 2014 D method (frictional voltage attenuation measurement method). was measured. The measurement conditions are as described above. Antistatic properties were evaluated according to the following criteria. ◎: Initial triboelectric voltage is -7000V or more 〇: Initial triboelectric voltage is -8000V or more and less than -7000V ×: Initial triboelectric voltage is less than -8000V
[0030] <Measurement of breaking strength and breaking elongation> In accordance with JIS L 1013, using an AGS-1KNG Autograph (registered trademark) tensile tester manufactured by Shimadzu Corporation, measurement was performed under the conditions of a sample thread length of 20 cm and a constant speed tensile test of 20 cm / min. The breaking strength (cN / dtex) was defined as the value obtained by dividing the maximum value of the load in the load-elongation curve by the fineness, and the elongation at that time was defined as the breaking elongation (%).
[0031] <Evaluation of spinning runnability> Spinning runnability was evaluated according to the following criteria. ◎: No yarn breakage after 10 hours of spinning 〇: Yarn breaks 1-2 times after 10 hours of spinning ×: Thread breakage 3 times or more after 10 hours of spinning
[0032] [Example 1] As an antistatic agent, an antistatic agent (“IonPhase hSTAT2” manufactured by Croda Japan) containing an organic metal salt (potassium trifluoromethanesulfonate) is used, polyethylene terephthalate and the antistatic agent are dried in a vacuum dryer, and the moisture content is 40ppm. Polyethylene terephthalate and an antistatic agent are used in chip blend for the sea part, and polyethylene terephthalate is used for the island part. Melt composite spinning was performed using a spinneret capable of forming a sea-island cross section. The ratio of the area occupied by the sea portion in the cross section of the fiber was set to 50%, the content of the antistatic agent in the sea portion was set to 5% by mass, and the content of the antistatic agent in the entire fiber was set to 2.5% by mass. Using two extruders adjusted to 280°C, polyethylene terephthalate and a chip blend of polyethylene terephthalate and an antistatic agent are separately extruded. Breaking elongation of yarn obtained by passing through an oiling agent guide, passing through a first godded roller set at a speed of 980 m / min and a temperature of 83°C, and a second godded roller set at a speed of 3600 m / min and a temperature of 135°C. was continuously drawn to 20 to 40%, and further wound with a winder at a speed of 3570 m / min to obtain an antistatic sea-island fiber of 33 dtex / 12 f. The breaking strength and breaking elongation of the obtained antistatic sea-island fibers were measured. Also, two multifilaments of the obtained antistatic sea-island fibers were combined and tubularly knitted (32 gauge) by a tubular knitting machine, and the antistatic property was evaluated using the obtained tubular knitted fabric.
[0033] [Example 2] An antistatic sea-island fiber was obtained in the same manner as in Example 1, except that the content of the antistatic agent in the sea portion was 6.0% by mass, and the content of the antistatic agent in the entire fiber was 3.0% by mass. Using the obtained antistatic sea-island fiber, the breaking strength and breaking elongation were measured. Further, a tubular knitted fabric was produced in the same manner as in Example 1, and the antistatic property was evaluated.
[0034] [Example 3] An antistatic sea-island fiber was obtained in the same manner as in Example 1, except that the content of the antistatic agent in the sea portion was 4.5% by mass, and the content of the antistatic agent in the entire fiber was 2.3% by mass. Using the obtained antistatic sea-island fiber, the breaking strength and breaking elongation were measured. Further, a tubular knitted fabric was produced in the same manner as in Example 1, and the antistatic property was evaluated.
[0035] [Example 4] An antistatic sea-island fiber was obtained in the same manner as in Example 1, except that the ratio of the area occupied by the sea portion in the cross section of the fiber was 67%, and the content of the antistatic agent in the entire fiber was 3.3% by mass. Breaking strength and breaking elongation were measured using the obtained antistatic sea-island fiber. Further, a tubular knitted fabric was produced in the same manner as in Example 1, and the antistatic property was evaluated.
[0036] [Comparative Example 1] Using a spinneret having a core-sheath shape in which the cross section of the fiber is composed of one core portion not exposed to the fiber surface and a sheath portion covering the core portion, the sea portion of Example 1 is used as the sheath portion, and An antistatic fiber was obtained in the same manner as in Example 1, except that the island portion was used as the core portion. Breaking strength and breaking elongation were measured using the obtained antistatic fiber. Further, a tubular knitted fabric was produced in the same manner as in Example 1, and the antistatic property was evaluated.
[0037] [Comparative Example 2] Example except that a chip blend of polyethylene terephthalate and an antistatic agent was spun using a spinneret having a circular cross section, and the content of the antistatic agent in the entire fiber was 3.0% by mass. An antistatic fiber was obtained in the same manner as in 1. Breaking strength and breaking elongation were measured using the obtained antistatic fiber. Further, a tubular knitted fabric was produced in the same manner as in Example 1, and the antistatic property was evaluated.
[0038] [Comparative Example 3] Same as Example 1, except that a spinneret having a fiber cross section of 1 cross-shaped portion / 2 fan-shaped portions was used, and the sea portion of Example 1 was changed to 1 cross-shaped portion and the island portion was changed to 2 fan-shaped portions. Similarly, an antistatic fiber having the shape shown in FIG. 1 was obtained. The breaking strength and breaking elongation were measured using the obtained antistatic fiber. Further, a tubular knitted fabric was produced in the same manner as in Example 1, and the antistatic property was evaluated.
[0039] [Comparative Example 4] The same as Example 1 except that the fiber cross section of Example 1 was changed to 3 US-shaped portions and 4 fan-shaped portions, and the sea portion of Example 1 was changed to 3 US-shaped portions and the island portion to 4 fan-shaped portions. Similarly, an antistatic fiber having the shape shown in FIG. 2 was obtained. Breaking strength and breaking elongation were measured using the obtained antistatic fiber. Further, a tubular knitted fabric was produced in the same manner as in Example 1, and the antistatic property was evaluated.
[0040] [Comparative Example 5] An antistatic fiber was obtained in the same manner as in Example 1, except that the content of the antistatic agent in the sea part was 4.0% by mass, and the content of the antistatic agent in the entire fiber was 2.0% by mass. Breaking strength and breaking elongation were measured using the obtained antistatic fiber. Further, a tubular knitted fabric was produced in the same manner as in Example 1, and the antistatic property was evaluated.
[0041] [Comparative Example 6] An antistatic sea-island fiber was prepared in the same manner as in Example 1, except that the content of the antistatic agent in the antistatic agent-containing polyethylene terephthalate was 7.0% by mass, and the content of the antistatic agent in the entire fiber was 3.5% by mass. got Breaking strength and breaking elongation were measured using the obtained antistatic sea-island fiber. Further, a tubular knitted fabric was produced in the same manner as in Example 1, and the antistatic property was evaluated.
[0042] [Comparative Example 7] An antistatic sea-island fiber was obtained in the same manner as in Example 1, except that the ratio of the area occupied by the sea portion in the cross section of the fiber was 33%, and the content of the antistatic agent in the entire fiber was 1.7% by mass. Breaking strength and breaking elongation were measured using the obtained antistatic sea-island fiber. Further, a tubular knitted fabric was produced in the same manner as in Example 1, and the antistatic property was evaluated. These results are shown in Table 1.
[0043]
table 1
[0044] All of the antistatic sea-island fibers obtained in Examples 1 to 4 had an initial frictional electrification voltage of -7000 V or higher, and had high antistatic performance, and were sufficiently satisfactory in terms of antistatic performance. [Industrial applicability]
[0045] The antistatic sea-island fiber of the present invention has good spinning operability and excellent antistatic performance, and can be suitably used as a lining when mixed with a polyester woven or knitted fabric to make an antistatic fabric. . [Description of symbols]
[0046] 1 cruciform 2 sector 3 American-shaped part 4 sector
Claims
1. An antistatic sea-island fiber, wherein island parts contain polyester and a sea part contains polyester and an antistatic agent, the antistatic sea-island fiber comprising a plurality of island parts not exposed on the surface of the fiber and a sea part covering the island parts, the content of the antistatic agent in the entire fiber is 2.2 to 3.3 mass%, the content of the antistatic agent in the sea part is 4.5 to 6.0 mass%, and the ratio of the area occupied by the sea part in the cross section of the fiber is 40 to 70%.
2. The antistatic islands-in-sea fiber according to claim 1, wherein the antistatic agent comprises potassium trifluoromethanesulfonate.
3. The antistatic sea-island composite fiber according to claim 1 or 2, wherein the total fineness is 10 dtex or more.
4. The antistatic sea-island composite fiber according to any one of claims 1 to 3, wherein the single yarn fineness is 1 to 10 dtex.
5. The antistatic sea-island composite fiber according to any one of claims 1 to 4, wherein the number of island parts is 10 to 40.